Interaction of hydrogen plasma with corroded silver surface - Mozetič, Miran (Informacije MIDEM, 1998)
Experimental investigation on discharage cleaning of corroded silver surface has been performed. Samples of silver with a thin and thick corroded layer were used. In the case of a thin layer, the surfce of pure silwer was contaminated with fingerprints. AES analysis showed that the layer with the thickness of 20 nm consisting of O, S, Cl and C was formed. In the case of a thick layer, a well corroded silver coin from 19th century was used. In this case, the thickness of the corroded layer was in the order of 0,1 mm and the EMPA investigation showed it was an agglomerate consisting of O, S, Cl, Si, C, Fe, Ti. All samples were exposed to a low pressure weakly ionized hydrogen plasma at the pressure of 1 mbar. Plasma parameters were measured with a double Langmuir probe and a calalytic probe. The electron temperature was 6eV, plasma density 2.10sup16 msup-3, and the degree od dissociation of hydrogen moleculs about 1%. Samples with the thin corroded layer were exposed to plasma for 10 minutes. AES analysis of the treated samples showed that all impurities were completely removed from the surface. The coin was exposed to hydrogen plasma at the same conditions, and the EMPA analysis showed that concentration of oxidizing impurities was lowered but other impurities still persisted. They could not be removed solely by treatments in plasma, but successive treatment in plasma and ultrasound bath. By the combination of both treatments we were able to decrease the concentration of any impurities below the detection limit of the EMPA.
Keywords: čiščenje; korozija; plazma; površine; srebro